2017
DOI: 10.1136/bmjsem-2016-000195
|View full text |Cite
|
Sign up to set email alerts
|

Unloading knee brace is a cost-effective method to bridge and delay surgery in unicompartmental knee arthritis

Abstract: BackgroundUnloading knee braces can provide good short-term pain relief for some patients with unicompartmental osteoarthritis (UOA). Their cost is relatively small compared with surgical interventions. However, no previous studies have reported their use over a duration of 5 years or more.MethodsUp to 8 years of prospective data were collected from 63 patients who presented with UOA. After conservative management with analgesia and physiotherapy, patients were offered an unloading brace. EQ-5D (EuroQol five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 8 publications
1
51
0
Order By: Relevance
“…Other unloading braces are typically focused on providing unicompartmental offloading of the TF joint [23][24][25][26][27][32][33][34] without addressing PF compartment loading. An important limitation of unicompartment offloaders is that as the offloading benefit is realized by one side of the TF joint, the opposite TF compartment experiences an increase in loading.…”
Section: Unloading Provided By the Tricompartment Unloadermentioning
confidence: 99%
See 3 more Smart Citations
“…Other unloading braces are typically focused on providing unicompartmental offloading of the TF joint [23][24][25][26][27][32][33][34] without addressing PF compartment loading. An important limitation of unicompartment offloaders is that as the offloading benefit is realized by one side of the TF joint, the opposite TF compartment experiences an increase in loading.…”
Section: Unloading Provided By the Tricompartment Unloadermentioning
confidence: 99%
“…As little as 5 deg varus/valgus malalignment can increase compressive loading in the TF compartment by up to 90% [29], so this redistribution of contact forces could increase the likelihood of the patient developing bicompartmental OA [28]. Similarly, braces designed to target the PF compartment do not address TF joint loading [35] and do not consistently provide clinical benefits [13]. However, the current analysis suggests the unloading benefits of the TCU brace may be experienced by all three knee joint compartments.…”
Section: Unloading Provided By the Tricompartment Unloadermentioning
confidence: 99%
See 2 more Smart Citations
“…Valgus knee bracing is found to effectively correct the lower limb force lines, release pain feelings and improve joint functions of KOA patients by optimizing their biomechanical axis [10][11][12][13]. Kirkley et al [14] showed that valgus knee bracing can effectively reduce the pain symptom and joint mobility of KOA patients.…”
Section: Introductionmentioning
confidence: 99%